Mitochondrial ATP-Sensitive K+ Channel Opening Increased the Airway Smooth Muscle Cell Proliferation by Activating the PI3K/AKT Signaling Pathway in a Rat Model of Asthma - Min Gao; Qinran Sun; Qingfa Liu (Canadian Respiratory Journal)
Abnormal proliferation of airway smooth muscle cells (ASMCs) leads to airway remodeling and the development of asthma. This study aimed to assess whether mitochondrial ATP-sensitive K+ (mitoKATP) channels regulated the proliferation of ASMCs by regulating the phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) pathway in asthmatic rats. Forty-eight Sprague Dawley rats were immunized with ovalbumin-containing alum to establish the asthma models. The ASMCs were isolated and identified by phase-contrast microscopic images and immunohistochemical staining for α-smooth muscle actin. The ASMCs were treated with a potent activator of mitoKATP, diazoxide, or an inhibitor of mitoKATP, 5-hydroxydecanoate (5-HD). Rhodamine-123 (R-123) was used for detecting the mitochondrial membrane potential (Δψm). The proliferation of ASMCs was examined by the MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assay. The protein and mRNA expressions of AKT and p-AKT were detected using western blotting and quantitative real-time PCR. The results showed that diazoxide enhanced the mitoKATP channel opening in ASMCs in the rat model of asthma, while 5-HD impeded it. Diazoxide also increased ASMC proliferation in the rat model of asthma, whereas 5-HD alleviated it. However, LY294002, a PI3K/AKT pathway inhibitor, reversed the functional roles of diazoxide in the proliferation ability of ASMCs in the rat model of asthma. Furthermore, treatment with diazoxide induced the phosphorylation of AKT, and treatment with 5-HD decreased the phosphorylation of AKT in ASMCs in the rat model of asthma. In conclusion, the mitoKATP channel opening increased the proliferation of ASMCs by activating the PI3K/AKT signaling pathway in a rat model of asthma.